PELAKU TINDAK PIDANA PEMERKOSAAN DENGAN KORBAN PENYANDANG DISABILITAS: Legal Review Of Perpetrators Of The Criminal Act Of Rape With Victims With Disabilities - Ayudia Farrasheniya; Vientje Ratna Multiwijaya (Reformasi Hukum Trisakti, 2026)
Legal review of perpetrators of rape crimes with victims with disabilities in Court Decision Number 67/Pid.Sus/2025/PN.Lbb. The legal issues addressed are the conformity of imposed sanctions with Article 15 paragraph (1) letter h of Law Number 12 of 2022. The research employs a normative approach with descriptive characteristics through case study analysis, examining primary legal materials including statutory regulations and court decisions, along with secondary legal materials. Research findings indicate that the sanctions imposed in the decision have not fully complied with the provisions for sentencing enhancement as regulated in Law Number 12 of 2022, as the judge only applied Article 285 of the Criminal Code without considering special enhancement for victims with disabilities. In conclusion, the application of sanctions has not been optimal in providing legal protection for persons with disabilities and does not fully reflect comprehensive punishment objectives. Judicial prudence is required in considering victim vulnerability aspects to impose fair and proportional sanctions